Mammary Microvessels are Sensitive to Menstrual Cycle Sex Hormones - Carmen Moccia; Marta Cherubini; Marina Fortea; Akinola Akinbote; Prasanna Padmanaban; Violeta Beltran‐Sastre; Kristina Haase (Advanced Science, 2023)
Abstract The mammary gland is a highly vascularized organ influenced by sex hormones including estrogen (E2) and progesterone (P4). Beyond whole‐organism studies in rodents or cell monocultures, hormonal effects on the breast microvasculature remain largely understudied. Recent methods to generate 3D microvessels on‐chip have enabled direct observation of complex vascular processes; however, these models often use non‐tissue‐specific cell types, such as human umbilical vein endothelial cells (HUVECs) and fibroblasts from various sources. Here, novel mammary‐specific microvessels are generated by coculturing primary breast endothelial cells and fibroblasts under optimized culture conditions. These microvessels are mechanosensitive (to interstitial flow) and require endothelial–stromal interactions to develop fully perfusable vessels. These mammary‐specific microvessels are also responsive to exogenous stimulation by sex hormones. When treated with combined E2 and P4, corresponding to the four phases of the menstrual cycle (period, follicular, ovular, and luteal), vascular remodeling and barrier function are altered in a phase‐dependent manner. The presence of high E2 (ovulation) promotes vascular growth and remodeling, corresponding to high depletion of proangiogenic factors, whereas high P4 concentrations (luteal) promote vascular regression. The effects of combined E2 and P4 hormones are not only dose‐dependent but also tissue‐specific, as are shown by similarly treating non‐tissue‐specific HUVEC microvessels.